2022
DOI: 10.3390/land11030335
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Critical Diffusion Factors of Public–Private Partnership and Social Policy: Evidence from Mainland Prefecture-Level Cities in China

Abstract: Cooperation between government and social capital is an important starting point in the supply-side reform of public services. It is also an effective practice in public governance innovation. Based on policy diffusion theory and event history analysis (EHA), this study analyzes panel data from 282 mainland prefecture-level cities in China from 2004–2020 to explore public–private partnerships’ critical diffusion factors. The study reveals that motivation factors, resource/obstacle factors, and external factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Relly (2012) found that a favorable environment for news media can have a significant influence on legislation adoption in United Nations member states [58], and this influence is also applicable to the CSRU pilot policy in China. The public opinion and publicity effect can help promote the diffusion of CSRU pilot policies [34,52], especially as the news media plays an important role in setting the policy agenda in China [59]. Therefore, public opinions and attitudes should also be considered in exploring the factors influencing the diffusion of the CSRU pilot policy.…”
Section: External Pressurementioning
confidence: 99%
“…Relly (2012) found that a favorable environment for news media can have a significant influence on legislation adoption in United Nations member states [58], and this influence is also applicable to the CSRU pilot policy in China. The public opinion and publicity effect can help promote the diffusion of CSRU pilot policies [34,52], especially as the news media plays an important role in setting the policy agenda in China [59]. Therefore, public opinions and attitudes should also be considered in exploring the factors influencing the diffusion of the CSRU pilot policy.…”
Section: External Pressurementioning
confidence: 99%